Le travail en chantier - Charest, Jean (Relations industrielles / Industrial Relations, 2004)
The article reviews the book, "Le travail en chantier," by Marcelle Duc.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

La mobilité de la main-d’oeuvre dans l’industrie de la construction au Québec : une double réalité - Charest, Jean (Relations industrielles / Industrial Relations, 2008)
L’industrie de la construction connaît une mobilité de la main-d’oeuvre particulièrement élevée en regard de la moyenne des autres secteurs de l’économie. En effet, le taux annuel des cessations d’emploi est pratiquement le double dans la construction par rapport à l’ensemble des secteurs d’activité économique. Cela s’explique par diverses caractéristiques de l’activité productive de cette industrie. Par ailleurs, cette mobilité doit être distinguée selon que l’on considère les déplacements de la main-d’oeuvre au sein même de l’industrie ou les départs permanents de cette industrie. Recourant à des données originales de Statistique Canada, nous présentons une analyse de certains facteurs explicatifs de cette double réalité. Nous nous intéressons notamment au cas du Québec qui offre un profil institutionnel particulier en matière de régulation du marché du travail., The construction industry has often been described in terms of its distinctive features, that is, its industrial organization, the specificity of its workforce, the nature of its work processes or its labour relations system. An important feature of the industry is unstable employment and the resulting high level of workforce mobility. Empirically, this industrial mobility is reflected in a rate of workforce mobility in the industry that is practically twice higher than in the economy as a whole. This is based on the mobility indicator of terminations of “permanent” employment during the course of one year as used by Statistics Canada. However, the usual statistical measure of workforce mobility expresses a break in the employment relationship for a given employer. This measure therefore does not necessarily describe adequately the reality of an industry with characteristics such as those found in the construction industry, since the Statistics Canada data do not indicate if the workers find other employment in the same or another sector. These important distinctions are rarely considered in either official statistics or the literature. For an industry whose labour market tends to be regulated on a sectoral basis, which is the case in Quebec, workforce mobility within the industry or sector itself does not have the same significance as permanent departures from the industry. The latter would represent a net loss of human capital. Considering the possible impacts on the workforce, employers and the industry in general, it is important to examine this phenomenon of high workforce mobility, to measure it, and to try to evaluate its causes and effects. This article thus seeks to understand, in particular, whether workforce mobility in the construction industry is truly exceptional. We will examine original comparative data for Quebec and Canada. More particularly, we have sought to distinguish between workforce mobility within the construction industry and mobility expressed through workforce departures to other sectors. The main results of our research indicate that construction workers’ movement to other sectors in Quebec is a real and significant phenomenon, although it is among the lowest when compared to other Canadian provinces. The proportions of construction industry workers who move to other economic sectors are similar to those observed for other industries. Thus, our data on this mobility correspond to certain explanatory factors found in the literature to explain workforce mobility, such as age and income level. In fact, in line with most studies identified in the literature on workforce mobility, the workers who leave the industry are younger than those in the industry as a whole. Moreover, it can also be suggested that they are more inclined to leave the industry if, in addition to being among the youngest, they are not highly skilled. In terms of income, our results are in line with the literature. On the one hand, mobility is more often correlated with low initial gains for workers, and on the other, a logical consequence is that mobility reflects the workers’ desire to improve their economic situation. It can also be hypothesized that changing sector will tend to also correspond to workers’ changing their occupations. This hypothesis is supported by two facts. First, most construction trades are very specific to the industry and as such, are not easily exported to other sectors. Second, the sectors to which workers who have left construction tend to move often have little to do with the latter (e.g., transportation, commerce, public services or manufacturing industries). Workforce mobility in the construction industry is an ongoing challenge for an industry with characteristics of production activity that often result in employment instability. Thus, how can workers be attracted to and retained by the industry which, year after year, has twice as many employment terminations as in other sectors? Our data suggest an initial conclusion regarding the conditions that should be put in place to minimize permanent departures from the industry. The workers recruited should be guaranteed a satisfactory number of working hours, which will provide them with an income level that is at least comparable to other sectors. The recruitment of workers who hold a diploma, as compared with workers without experience or specific knowledge of the industry, also seems to have a positive effect on their retention. Our data also suggest that sectoral regulation of the workforce, and particularly the centralized management of benefits, are organizational features that mitigate certain disadvantages of employment instability for workers. In other words, it is argued that this model of sectoral regulation results in workforce management that reconciles the imperatives of the high mobility specific to this sector while at the same time ensuring a degree of economic security for workers., La industria de la construcción conoce une movilidad de la mano de obra particularmente elevada comparativamente a otros sectores de le economía. En efecto, la tasa anual de cesación de empleo es prácticamente el doble en la construcción comparativamente al conjunto de sectores de actividad económica. Esto se explica en razón de las diversas características de la actividad productiva de esta industria. Es más, esta movilidad debe ser distinguida según que se considere los desplazamientos de mano de obra dentro de la misma industria o los alejamiento permanente de esta industria. Utilizando datos originales de Estadísticas Canadá, presentamos un análisis de ciertos factores explicativos de esta doble realidad. Nos interesamos en especial al caso de Quebec que presenta un perfil institucional particular en materia de regulación del mercado de trabajo.

Vocational Training and the Labour Market in Liberal and Coordinated Economies - Bosch, Gerhard; Charest, Jean (Industrial Relations Journal, 2008)
In recent decades, the differences between the education and training systems in the liberal and coordinated market economies have increased. It is not possible to understand such different developments by focusing exclusively on the internal dynamics of vocational and general education systems. Vocational education and training (VET), and particularly apprenticeship systems rather than school-based VET, are deeply embedded in the different national production, labour market, industrial relations and status systems. In order to contribute to a better understanding of the dynamics of VET, we examine recent developments in general and vocational training and its links to the labour and product market in five contrasting countries, namely, Denmark, Canada, Germany, Korea and the USA. In particular, differences in industrial relations, welfare states, income distribution and product markets are the main reason for the persistent high level of diversity in vocational training systems. The difference can perhaps be summarized as follows: in the coordinated market economies, the modernisation of vocational training is seen as a contribution to innovation in the economy, while in liberal market economies, it is seen as a siding into which weaker pupils can conveniently be shunted.